Irrational beliefs surrounding the diagnosis of breast cancer in young Chinese women: An observational study. Issue 9 (5th March 2021) - Li, Xingxing; Zhao, Mingming; Dong, Xiaomeng; Zhao, Qiyuan; Zhang, Xiuwei
Abstract : Abstract: An irrational belief is the direct cause of negative emotions and behavioral disorders in patients with breast cancer. Thus, this article examines these patients' irrational beliefs, which helps improve the emotions and behavioral disorders of breast cancer patients. Chinese breast cancer patients have unique irrational beliefs due to the influence of Chinese traditional culture. To understand the irrational beliefs surrounding breast cancer diagnosis in young Chinese patients, we conducted an interpretative phenomenological study. Semi-structured interviews were conducted in young Chinese breast cancer patients. According to Colaizzi method modified by Edward and Welsh, transcribed interviews were analyzed to understand patients' irrational beliefs. Based on the theoretical framework, this study adopted interpretative phenomenology. Interpretive description was used to construct participants' experiences of irrational beliefs. Thematic sufficiency was confirmed after 17 interviews. Owing to the lack of knowledge about breast cancer, all participants were more susceptible to traditional Chinese culture, empiric theory, family reassurance, and healthcare providers' behaviors, leading to patients' irrational beliefs, negative emotions, and behavioral disorders. This research confirms that irrational beliefs in young Chinese breast cancer patients are profoundly influenced by traditional Chinese culture. Chinese healthcare providers can use this information to provide targeted nursing, supportive services, and research, and help women identify their beliefs and understand how these beliefs affect their health.